2004
DOI: 10.1023/b:bile.0000013711.32890.5d
|View full text |Cite
|
Sign up to set email alerts
|

Decoloration of a Carpet Dye Effluent Using Trametes Versicolor

Abstract: Although a non-sterile, undiluted carpet dye effluent (containing two anthraquinone dyes) did not support growth of Trametes versicolor, the pre-grown fungus removed 95% of its color in shake-flasks after 10 h of incubation. After decoloration, the COD of the cell-free supernatant increased and the toxicity was unchanged as determined by the Microtox assay using Vibrio fischeri. Decoloration rates decreased when either glucose alone or Mn2+ and glucose were added. T. versicolor, immobilized on jute twine in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…In a previous study the detoxification ability of this fungus was also reported by Apohan and Yesilada (2005). Ramsay and Goode (2004) reported the dye effluent decolorization ability of T. versicolor. However, in some studies the toxicity remained unchanged, decreased or increased after biological decolorization Shin et al 2002;Ramsay and Goode 2004).…”
Section: Resultssupporting
confidence: 55%
“…In a previous study the detoxification ability of this fungus was also reported by Apohan and Yesilada (2005). Ramsay and Goode (2004) reported the dye effluent decolorization ability of T. versicolor. However, in some studies the toxicity remained unchanged, decreased or increased after biological decolorization Shin et al 2002;Ramsay and Goode 2004).…”
Section: Resultssupporting
confidence: 55%
“…Several methods have been used or proposed for color removal from wastewaters. This includes biological aerobic (e.g., activated sludge, SBR, biofilter) [8][9][10] or anaerobic (e.g., UASB) [1,11] treatments, enzymatic biodegradation (actinomycetes, fungi) [12], chemical oxidation (H 2 O 2 /Fe 2? (Fenton), e.g., hypochlorite), [13,14] or reduction (e.g., Fe 0 ) [15], electrochemical oxidation (e.g., O 3 /UV, O 3 /H 2 O 2 , O 3 /UV/H 2 O 2 , H 2 O 2 /UV) [16,17], photodegradation (e.g., TiO 2 /UV, photo-Fenton) [18,19], adsorption (e.g., activated carbons, silica, biosorbents) [20,21], membrane separation (e.g., microfiltration, ultrafiltration, nanofiltration) [22], chemical coagulation/flocculation (e.g., aluminum, iron, or calcium salts) [23], and electrolytic treatments, which include electroflocculation [24], and/or electrocoagulation [25][26][27][28], and electro-oxidation [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…After the establishment of T. versiolor on jute twine, which had been previously found to be a good immobilization support [16,19], the sequential batch decoloration of amaranth in the RBC was evaluated. After a fresh volume of decoloration medium (i.e., 50 mg/l amaranth and 1 g/l glucose in water alone) replaced the spent growth medium, there was a lag of over 20 h with amaranth decolorized at an overall rate of 1.04 mg/l per h (Fig.…”
Section: Sequential Batch Operationmentioning
confidence: 99%
“…Rotating biological contacting (RBC) reactors are a likely choice to treat dye effluents as they allow surface immobilization of WRF such as Trametes versicolor [16]. Immobilized cultures tend to have a higher level of activity and are more resilient to environmental perturbations such as pH, or exposure to toxic concentrations than suspension cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation